Intelligent Fault Detection and Diagnostics - Lemma, T.A. (Springer Verlag, 2018)
This chapter contains the last part of the research methodology. On the bases of the methods discussed in Chaps. 3 and 4, it develops the planned FDD system. Â© 2018, Springer International Publishing AG.